QUALITY MANAGEMENT IN SURGICAL DISCIPLINES (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In continuation to our previous article 1 regarding the significance of clinical protocols in surgical disciplines, we would like to present the next two of our protocols, designed after meticulous study of the related literature and after the evaluation of worldwide experts opinion on the subject 2-12. We would like to emphasize again the fact that, clinical protocols act both as a medical as well as a managerial tool, aiming at the improvement of clinical services provided to our patients, with the application of the means available each time at the least possible cost The rationale behind is that since health treatments have a cost and resources are limited, the integration of managerial and financial efficiency within clinical efficiency is crucial 13, 14, 15,16. As Bachtsevani et al. 14 put it, it seems the use of evidence-based guidelines can improve outcomes in relation to organizations in the sense of decreased admission rates, length of stay, and less resource utilization, which reduces costs. Such monitoring mechanisms intend to evaluate, reassess and improve the clinical care not only in terms of outcomes but also in financial terms for the benefit of the patient welfare, and the hospital as an organization denoting in this way the significance of evidence-based medicine 15,17 Evidence has also shown that the greater the strength of the evidence incorporated, the greater the quality of the guideline and the greater its potential to maximize the use of resources and improve quality of healthcare18.